The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1080/15230406.2021.1933595
|View full text |Cite
|
Sign up to set email alerts
|

The role of user context in the design of mobile map applications

Abstract: Mobile map applications are typically used by a broad range of users. Users can be diverse in their context attributes (e.g. map use experience, activities during map use), and several previous user experience (UX) studies have focused on understanding how some contextual factors influence the UX for designing maps that satisfy users' needs. A need for research remains to evaluate the relationship between user context, UX, and variants of mobile map element design. In this article, we present our research inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 37 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Additionally, Khalaf & Ja'afar (2020) argued that quality characteristics such as userfriendliness, comfort, convenience, and accessibility are factors that influence product quality. Additionally, Bartling et al (2021) highlighted the importance of user context and user experience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, Khalaf & Ja'afar (2020) argued that quality characteristics such as userfriendliness, comfort, convenience, and accessibility are factors that influence product quality. Additionally, Bartling et al (2021) highlighted the importance of user context and user experience.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lavie et al (2011) evaluated electronic map navigation displays and found a significant effect on color schema and a shorter response time of the gray color scheme than that of the mild and bold schemes. Bartling et al (2021) tested three base map styles of Mapbox Dark, Mapbox Streets, and Mapbox Satellite Streets in terms of task success, comfort, and confidence ratings. Although the Mapbox Streets base map attained higher task success scores, the three base map styles had somewhat similar comfort and confidence ratings.…”
Section: Dark Maps and Usabilitymentioning
confidence: 99%
“…According to the design principals of Digital Development [72], we developed both, the conceptual framework as well as the 'Bürgercockpit'-application in a collaborative, incremental and iterative process from diverse disciplines and constant reference to user needs, starting in 2012 [70,[73][74][75]. We applied a cross-platform approach to ensure uniform access across a variety of devices (e.g., web, mobile, and desktop platforms), which helps minimizing development and maintenance costs since only one single code base exists.…”
Section: The 'Bürgercockpit'-application Piloting Phase and Commercia...mentioning
confidence: 99%